Lifelink development of a portable telehealth device for remote monitoring of biomedical signals - Broma, Julius Miguel J.; Santos, Arlan Roie A. (2009)
Telemedicine is the application of telecommunications technology in providing healthcare services and facilitating health information exchange between two or more remote locations. It involves diagnosis, immediate treatment, and medical records of patients. Most rural and even some urban areas in the Philippines have limited or no access to quality health services. The growing number of Health care professionals leaving the country further aggravates the problem. A sound solution is the development of a local telemedical system. LifeLink is the third phase in the telemedical initiative of The National Telehealth Service Program. The first phase was TELEMED: A Linux-based Telemedical System and the second phase was Telemed II: A Single Board Computer Implementation of a Linux-based Telemedical System. The main goal of this project is to implement a remote health monitoring device (LifeLink) consisting of a computer workstation (the RxBox) and biomedical modules that acquire patient health data. The RxBox was developed using the ASUS Eee Box running in the Linux operating system. Lifelink employs voice and data transmission using Voice over IP (VoIP). Based on Telemed II,the RxBox software was improved to allow videoconferencing and session recording. An LCD touch screen was integrated with the RxBox to effectively utilize the features of the RxBox software. The GUI was tested for usability by the end users along with a human factors consultant. A set of medical-grade biomedical modules was used to monitor the condition of the patient in terms of electrocardiogram (ECG), pulse rate, percent oxygenation of the blood (%SpO2), and blood pressure (BP). The off-the-shelf modules were integrated to the LifeLink system through USB (ECG, %SpO2), and blood pressure). An Application Programming Interface (API) was also developed in Python to facilitate data acquisition from the modules. The interconnection and API were designed to follow the following medical standards: device communication, P1073.3 transport profile (for sensor module connectivity), and EDF (for time series data). The project software was developed and maintained using pydoc, a Python documentation generator system, and Subversion (SVN), a version control system that maintains multiple versions of files to facilitate collaboration with other developers of the telehealth program. Finally, the modules were benchmarked with medical_grade equipment in the UP Philippine General Hospital (PGH).
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Biomedical engineering; Signal processing -- Digital techniques; Biomedical signals; LifeLink; Portable telehealth device